Use of venous-venous extracorporeal membrane oxygenation in the treatment of postpartum pulmonary hypertension crisis. (March 2023) - Jiang, Yongpo; Lou, Minjuan; Chu, Xiaoqiong; Zheng, Dan; Cai, Minjie; Zhao, Weili; Lin, RongHai; Zhang, Sheng
The incidence of heart disease in pregnancy ranges from 0.5% to 3.0% and is regarded as one of the top three causes of maternal death. The mortality rate of patients with pulmonary hypertension and Eisenmenger syndrome is as high as 16.7%–50%. Changes in haemodynamics during pregnancy and childbirth increase the burden on the heart, and induced pulmonary hypertension crisis is one of the main causes of maternal death. Extracorporeal Membrane Oxygenation (ECMO) is the last-resort treatment strategy to treat patients with pulmonary hypertension crisis. We report a ventricular septal defect in a pregnant woman with pulmonary hypertension and Eisenmenger's syndrome, which is a postpartum pulmonary hypertension crisis that leads to respiratory and circulatory disorders. The patient was successfully treated with venous-venous extracorporeal membrane oxygenation.